Management of an infected cementless cup with prosthetic retention and antibiotic therapy in a dog. (11th August 2014) - Dan, B. J.; Kim, S. E.; Pozzi, A.
<x xml:space="preserve">Abstract</x> A two‐year‐old Rottweiler presented for acute onset of a right hindlimb lameness 20 weeks after a cementless total hip replacement (THR) and 16 weeks after open reduction to address luxation of the THR. Radiographs revealed periosteal proliferation of the medial acetabulum and a stable implant. Synovial fluid cytology was consistent with inflammatory joint fluid. Treatment consisted of surgical debridement and intravenous and oral antibiotics. THR implants were not removed. Culture of tissue removed from the THR site yielded growth of Pseudomonas and Staphylococcus species. Lameness resolved 2 months after surgery. Twenty months after surgery, the dog was exercising normally with no clinical lameness and pelvic radiographs revealed no evidence of implant loosening and markedly decreased periosteal reaction. To the authors' knowledge, this is the first report of an infected THR site successfully treated without prosthesis explantation in the dog.